Optimalisasi Interior Ruang Keterampilan SLB-C Karya Bhakti Dengan Pendekatan Behavior Tunagrahita - Afni, Fauziyah; Widiatmoko, Didit; Azhar, Hanif; Nurhadiansyah, Mahendra (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
Education is an important thing in life. Based on SDGs Number 4 on quality education, every child has the right to receive the same education, just like children with special needs. In the education system, children with special needs are often overlooked, these problems include a lack of adequate facilities and infrastructure such as skill spaces to support children's creativity, and inadequate interior elements. This research uses a design thinking approach involving five stages: empathize, define, ideate, prototype, and testing. Data collection through observation, interviews, questionnaires, visual observations, and literature studies. Then the data collected was analyzed using SWOT analysis. The result is that using good interior elements can provide positive sensory stimulation for students, especially those with special needs or the disabled. The benefits of this research can provide a reference for designing the interior of the skill room for children with disabilities that aligns with existing standards.